A New Automatic Nonlinear Optimization-Based Method for Directional Ocean Wave Spectrum Extraction From Monostatic HF-Radar Data - Shahidi, Reza; Gill, Eric W. (IEEE journal of oceanic engineering, 2021)
The extraction of oceanic wave spectrum information from radar data has been a challenging problem that has been the subject of a vast amount of research over the past several decades. This research has resulted in a multitude of approaches to extract ocean wave spectra from Doppler spectrum returns. One common feature of many of these methods is the reduction of the wave spectrum extraction problem from a nonlinear problem to a linear one. In this article, a new approach is introduced, which does not linearize the Fredholm integral equation relating the ocean wave spectrum to the radar Doppler spectrum, but instead maintains its nonlinear nature. Also, unlike previous nonlinear optimization solutions, the proposed method is automatic in the sense that no regularization parameters have to be manually set purely dependent on the radar data from which the ocean wave parameters are being extracted, thereby reducing the need for human intervention in the wave spectrum extraction process. In addition to describing this new method for wave spectrum extraction, this article presents results from a case study on field data from Argentia, NL, Canada, comparing the oceanographic parameters obtained with the proposed method to those recorded by in situ buoy instrumentation. The significant wave height calculated from ocean wave spectra extracted via the method are found to match with those from the buoy, whereas the values of other oceanographic parameters, such as wave period and direction extracted using the proposed method, are less accurate potentially due to the low quality of data available to test the method.